A novel evaluation of the effect of lanthanum exposure on plant populations. (July 2018) - Zhang, Fan; Li, Yihang; Shi, Yu; Wang, Lihong; Zhou, Qing; Huang, Xiaohua
Abstract: The accumulation of rare earth elements (REEs) in the environment has recently become a new environmental problem. There have been many studies about the effects of REEs on plant at the individual, organ, cellular and genetic levels. Plants exist in populations under natural conditions, but little is known about the effects of REEs on plant populations. In this study, the effects of lanthanum (III) [La(III)] on the root module growth of soybean ( Glycine max L) populations at different densities were investigated by simulating La(III) pollution. Results showed that at La(III) concentrations of 0.40 and 1.20 mM, both the root module growth parameters and leaf photosynthesis parameters were decreased, with 1.20 mM of La(III) causing a more significant decrease. In addition, the above parameters in low-density soybean populations decreased more significantly than those in high-density soybean populations. The above results show that the inhibitory effects of 0.40 and 1.20 mM of La(III) on the growth of root modules are closely related to the inhibition of photosynthesis in soybean population. Moreover, the inhibitory effect of La(III) on the growth of root modules of soybean population is enhanced as the La(III) concentration increases, while is weakened as plant population density increases. This study would provide a reference for the further research on the ecotoxicology of REEs, and show a new perspective and basis for the objective assessment of the environmental risks of REEs. One sentence summary: La(III) pollution affects the root module growth and photosynthesis in soybean populations, and the effects vary depending on soybean population densities. Graphical abstract: Image Highlights: A new experiment at plant population scale was designed to evaluate effects of REEs. La (III) effects on the root modules varied with soybean population density. It was proved that changes in root modules were related to photosynthesis. It was proved that changes in photosynthesis were related to La content in plants.